Implementasi Digital Marketing pada UMKM Donat Kekinian (Rasadonat) dalam Upaya Membangun Strategi Pemasaran - Mohammad Ridho Permana; Dira Ernawati (Jurnal Pengabdian Dian Mandala, 2023)
Digital Marketing is a marketing or promotional technique for a product through digital media or the internet which aims to attract consumers or potential consumers quickly and massively. In an era that is all digital and is increasingly developing over time, implementing digital marketing will be a very effective marketing strategy for community businesses or MSMEs. Therefore, RasaDonat MSMEs must implement and apply digital marketing as one of their product marketing strategies so that they do not only rely on conventional marketing. This research was conducted with the aim of finding out the implementation of digital marketing at RasaDonat MSMEs as a marketing strategy in an effort to face intense business competition as a result of the increasingly massive development of the digital era. This research was conducted using qualitative research methods, namely data collection methods using observation and literature study methods. The results of this research are the implementation of digital marketing at RasaDonat MSMEs which consists of creating brand guidelines, creating Google My Business, creating social media for product promotion and marketing, creating a website to make product marketing easier, creating commercial articles that are SEO friendly, creating marketing campaigns, as well as creating paid marketing for product promotion and marketing.